MODEL OF ANALYSIS AND INTERPRETATION OF IMAGES AND PHOTOGRAPHS AS A PART OF INTERACTIVE TEACHING STUDENTS FROM THE HIGH SCHOOL STAGE (Journal of Educational Sciences, 2018)
The article examines the possibilities of contemporary pedagogy of combining traditional models of teaching with the incorporation of interactive methods and techniques. The diversity of creative approaches in the teaching of lessons is a prerequisite for variance and focusing the attention of the students. The teaching with art resources and application of stimulant material, subject to further analysis by the students, actively involves them in studying and allows the development of perception, culture and values.The text presents an exemplary model for the analysis of images in a history lesson at high school stage (8th grade ). Our choice is random, and the text does not claim to be complete or scientifically strict. It aims to serve as an example in teaching practice and can be improved or supplemented by teachers, students or a particular context. The process is academic as well as creative and our professional flair, ability and courage to provoke ourselves and our students to think in a different way, are responsible for this exemplary version.Key words: analysis of image, photographs, history, stimulant material, Visual sociology